SYTL2 promotes metastasis of prostate cancer cells by enhancing FSCN1-mediated pseudopodia formation and invasion - Li, Zean; Tao, Yiran; Gao, Ze; Peng, Shirong; Lai, Yiming; Li, Kaiwen; Chen, Xu; Huang, Hai (Journal of translational medicine, 2023)
Metastatic prostate cancer (mPCa) has a poor prognosis with limited treatment options. The high mobility of tumor cells is the key driving characteristic of metastasis. However, the mechanism is complex and far from clarified in PCa. Therefore, it is essential to explore the mechanism of metastasis and discover an intrinsic biomarker for mPCa. Transcriptome sequencing data and clinicopathologic features of PCa from multifarious public databases were used to identify novel metastatic genes in PCa. The PCa tissue cohort containing 102 formalin-fixed paraffin-embedded (FFPE) samples was used to evaluate the clinicopathologic features of synaptotagmin-like 2 (SYTL2) in PCa. The function of SYTL2 was investigated by migration and invasion assays and a 3D migration model in vitro and a popliteal lymph node metastasis model in vivo. We performed coimmunoprecipitation and protein stability assays to clarify the mechanism of SYTL2. We discovered a pseudopodia regulator, SYTL2, which correlated with a higher Gleason score, worse prognosis and higher risk of metastasis. Functional experiments revealed that SYTL2 promoted migration, invasion and lymph node metastasis by increasing pseudopodia formation in vitro and in vivo. Furthermore, SYTL2 induced pseudopodia formation by enhancing the stability of fascin actin-bundling protein 1 (FSCN1) by binding and inhibiting the proteasome degradation pathway. Targeting FSCN1 enabled rescue and reversal of the oncogenic effect of SYTL2. Overall, our study established an FSCN1-dependent mechanism by which SYTL2 regulates the mobility of PCa cells. We also found that the SYTL2-FSCN1-pseudopodia axis may serve as a pharmacological and novel target for treating mPCa.